Lightning-induced transient effects in hybrid PV–wind system and its mitigation - Khurshid, Zmnako Mohammed (2018)
Lightning strikes cause current injection into the hybrid PV–wind system at the point of contact. Overvoltage generated due to lightning travels along the system where it can affect expensive equipment in the hybrid PV–wind system. The literature review examines related previous works and identifies the gaps created by earlier works that have focused only on the problems associated with the lightning effects on the PV and WT systems either theoretically or experimentally. Studies also have focused on a single type of RE source and not on hybrid systems. The current study fills the gap concerning the lightning-induced transient effect on a 4.1 MW grid-connected hybrid PV–wind system and the mitigation of the lightning effect using the Power Systems Computer Aided Design (PSCAD) software. The system consists of a 2 MW PV farm, a 2.1 MW wind farm, battery system and loads which are all connected to a 33 kV grid along with a 0.480 kV AC bus and a boost interfacing transformer. In addition, the Heidler function was modelled to generate different lightning currents using the software mentioned above. In this research, transient effects simulation and analysis due to direct lightning strikes to the system were conducted, three points of the hybrid system were selected to observe the transient overvoltage when each point was subjected to lightning strokes separately. The simulation results were obtained for different lightning current waveforms such as 8/20 μs, 10/350 μs, negative first stroke, negative subsequent stroke and positive stroke with and without lightning protection system (LPS) in several simulation cases. In addition, surge protective devices (SPDs) have been developed based on the European Commission for Electrotechnical Standardization (CENELEC) standard with the most appropriate ratings for the threat level and the equipment/component specification of the hybrid system to investigate mitigation of the lightning transient to an acceptable level. The results showed that the connected SPDs to the system can successfully clamp the generated transient overvoltages due to lightning for all simulation cases, except the SPDs connected at the DC side of PV system fail to clamp the generated overvoltage in the case with 5% of positive stroke lightning current. On the basis of the simulation results, the recommendations have been proposed to developers of lightning protection. The research objectives were achieved through simulation and analysis, findings of this research can be a useful guideline towards the application of a lightning protection standard for the hybrid PV–wind system.